Low-velocity impact response of carbon fibre composites with novel liquid Methylmethacrylate thermoplastic matrix - Bhudolia, Somen K. (2020)
Experimental investigations were carried out to determine the low-velocity impact behaviour of carbon fibre composites with novel liquid Methylmethacrylate (MMA) thermoplastic matrix, Elium®. The load, deflection and the energy attributes under impact are studied in detail and the baseline comparison is carried with the carbon fibre composites with epoxy matrix. The quasi-isotropic non-crimp carbon fabric (NCCF) laminates were impacted at 25 J, 42 J and 52 J impact energies and the material response of both the composite configurations were studied. The composite laminates have shown less catastrophic damage at a high energy level (52 J) and around 10% higher peak load was observed. Structural integrity as measured from the load-deflection curve demonstrated up to 53% increase for Thin NCCF Elium composite compared to their counterpart composites with epoxy matrix. Significant energy absorption (56%) before the onset of major failure mostly through elastic-plastic deformations was observed for thin NCCF Elium® composite. Impact results at different energies showed the strain sensitivity of Elium® microstructure with the improved performance with increasing impact energy. From the detailed fracture and damage analysis of the impacted samples, the failure mechanisms were deduced for the novel Thin NCCF Elium® and epoxy composites.